Association between e-cigarette use and sleep deprivation in U.S. Young adults: Results from the 2017 and 2018 Behavioral Risk Factor Surveillance System. (January 2021) - Kianersi, Sina; Zhang, Yijia; Rosenberg, Molly; Macy, Jonathan T.
Highlights: Electronic cigarette use might be related to sleep deprivation in young adults. Former users were more likely to report sleep deprivation compared to nonusers. The association became stronger when comparing current users with nonusers. The association remained even after adjusting for confounders, e.g. alcohol use. Abstract: Background: Few studies have assessed the association between e-cigarette use and sleep deprivation. This is an important question given the rapid increase in e-cigarette use among young adults in recent years. Purpose: To determine whether e-cigarette use is associated with sleep deprivation in a sample of young (18–24 years-old) American adults. Methods: We used pooled cross-sectional data from the 2017 and 2018 Behavioral Risk Factor Surveillance System (BRFSS), selecting respondents aged 18 to 24 from forty-one states and U.S. territories that included the e-cigarette and sleep modules in the interview (N = 19, 701). Poisson regression models tested the relationship between e-cigarette use and sleep deprivation. We adjusted for sociodemographic variables, physical activity, mental health, BMI, smokeless tobacco products use, alcohol drinking, and smoking. Results: In the pooled dataset, the weighted prevalence of current or former e-cigarette use was 47% and 35% of participants self-reported sleep deprivation. After adjusting for confounders, former e-cigarette users were 1.17 times more likely to report sleep deprivation, compared to never users (95%CI: 1.06, 1.29). The prevalence ratio for self-reported sleep deprivation increased to 1.42 (95%CI: 1.23, 1.65) for everyday users, compared to never e-cigarette users. Conclusions: These findings suggest that e-cigarette use might be related to sleep deprivation in young adults. Future longitudinal studies should assess the causal and dose–response nature of this relationship.